2015
DOI: 10.3390/su7010947
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Financial Comparison between Organic and Conventional Farming in Sicilian Lemon Orchards

Abstract: Abstract:Sicily has a long tradition in citrus fruit cultivations that with vineyard and olive tree represent the main Mediterranean tree crops. In this paper we have evaluated the economic and financial sustainability of lemon production, both in organic farming and in conventional farming; the two systems differing just for inputs utilized in production process. Economic analysis has been carried out in a representative case study located in the Sicilian northwestern coast, considering an orchard economic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 70 publications
2
37
1
3
Order By: Relevance
“…In our study, fertilizer costs for EFF per ha were higher than for other farming techniques. This finding is inconsistent with the result of Sgroi et al [59], who found that CF had higher fertilizer costs when compared to organic one. The reason for the higher fertilizer costs in this area might be caused by the use of low quality organic fertilizer, which led not only to less crop production but also caused higher costs.…”
Section: Cost and Benefits Of The Three Farming Techniquescontrasting
confidence: 57%
“…In our study, fertilizer costs for EFF per ha were higher than for other farming techniques. This finding is inconsistent with the result of Sgroi et al [59], who found that CF had higher fertilizer costs when compared to organic one. The reason for the higher fertilizer costs in this area might be caused by the use of low quality organic fertilizer, which led not only to less crop production but also caused higher costs.…”
Section: Cost and Benefits Of The Three Farming Techniquescontrasting
confidence: 57%
“…However, in the study of Acs et al (2007), the effect of higher prices was mitigated by the lower yields and by the higher variable costs (in particular, labour costs). A better profitability of organic farms was also found by Sgroi et al (2015b). These authors studied farms growing lemon orchards.…”
Section: Discussionmentioning
confidence: 75%
“…The joint application of the economic and financial approach for the assessment of affordability and sustainability management can also give significantly different results between the two approaches, as demonstrated for other sectors by several studies (Greenberg et al, 1986;Kwon, 1989;Dechow, 1994;Russell, 2009;Iotti and Bonazzi, 2014b;Sgroi et al, 2015). This situation occurs particularly in SMEs characterized by absorption of working capital (Glancey, 1998;Kieschnick et al, 2008).…”
Section: Introductionmentioning
confidence: 98%